The Connection of Pedagogical and Information Communication Technologies in the Modern Training of Future Teachers of the Korean Language - Men Svetlana Rodionovna (International Journal on Integrated Education, 2023)
Digital transformation in education, namely the use of modern technologies to improve the quality of university education, is determined by the optimization of teacher-student interaction, which leads to the progressive movement of the educational process towards the development of self-sufficient personality for self-education and independent solution of cognitive problems arising at the same time, able to quickly and independently acquire knowledge and critically comprehend them.